Transparency in Central Bank Operations in the Foreign Exchange Market - Enoch, Charles (IMF Policy Discussion Papers; Policy Discussion Paper, 1998)
Transparency in the economic sphere involves making public sector action visible and understandable to the private sector. Transparency in central bank operations can be seen a complement to the greater transparency being established in policy formulation. Among the most important areas in this regard and the central bank's operations in the foreign exchange market. This paper looks at the respective roles of overt and covert foreign exchange market operations, and considers that each may be appropriate under particular conditions. Reconciling covert operations with transparency requires rules for full disclosure with as short a lag as possible.